On necessary optimality conditions in discrete control systems - Mardanov, M. J.; Melikov, T. K.; Mahmudov, N. I. (Taylor & Francis Ltd, 2015)
The paper deals with a nonlinear discrete-time optimal control problem with a cost functional of terminal type. Using a new variation of the control and new properties of optimal controls, we prove the linearised optimality conditions extending such classical optimality conditions. Along with this, various optimality conditions of quasi-singular controls are obtained. Finally, the examples illustrating the rich content of the obtained results are illustrated.
Keywords: discrete system; optimality conditions; maximum principle; optimal control